2017
DOI: 10.1111/epi.13778
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammation imaging markers for epileptogenesis

Abstract: Epilepsy can be a devastating disorder. In addition to debilitating seizures, epilepsy can cause cognitive and emotional problems with reduced quality of life. Therefore, the major aim is to prevent the disorder in the first place: identify, detect, and reverse the processes responsible for its onset, and monitor and treat its progression. Epilepsy often occurs following a latent period of months to years (epileptogenesis) as a consequence of a brain insult, such as head trauma, stroke, or status epilepticus. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 47 publications
(105 reference statements)
5
36
0
Order By: Relevance
“…24 Previous studies have shown increased TSPO binding in several ep ilepsy syndromes. 24 Previous studies have shown increased TSPO binding in several ep ilepsy syndromes.…”
Section: Discussionmentioning
confidence: 97%
“…24 Previous studies have shown increased TSPO binding in several ep ilepsy syndromes. 24 Previous studies have shown increased TSPO binding in several ep ilepsy syndromes.…”
Section: Discussionmentioning
confidence: 97%
“…29,30 Here, we describe the evolution of tracer binding to mGluR5, GABA A receptors, and microglia and astroglia markers during epileptogenesis and chronic epilepsy in the lithium-pilocarpine post-SE model in rats. Imaging biomarkers are of great interest as they enable several in vivo measurement in a minimally invasive manner and allow visualization of molecular pathways involved in epileptogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging biomarkers are of great interest as they enable several in vivo measurement in a minimally invasive manner and allow visualization of molecular pathways involved in epileptogenesis. 29,30 Here, we describe the evolution of tracer binding to mGluR5, GABA A receptors, and microglia and astroglia markers during epileptogenesis and chronic epilepsy in the lithium-pilocarpine post-SE model in rats. The use of in vitro autoradiography enabled direct quantification and comparison of all tracers in brain slices from the same animals for each time point.…”
Section: Discussionmentioning
confidence: 99%
“…This would allow patient stratification to test the candidate anti-inflammatory drugs and for designing affordable and adequately powered antiepileptogenesis trials, and to monitor treatment response. In this context, much progress has been made and several noninvasive inflammation-related humoral 44,[146][147][148][149] (blood/cerebrospinal fluid) and imaging measures [150][151][152][153][154][155][156][157] have been identified ( Table 2). Such biomarkers could be used to increase the sensitivity and precision of the available clinical indicators.…”
Section: Discussionmentioning
confidence: 99%